Comparison between methods for sizing building cold water systems: a bibliometric survey - Leite, Rafael Krüegel; Paula, Heber Martins de; Silva, Wellington Andrade da (Brazilian Journal of Production Engineering, 2026)
Even with the update of NBR 5626 in 2020, the sizing of Cold-Water Building Systems (CWBS) is still mostly carried out using empirical methods, particularly the German weighting method. This article presents a systematic literature mapping, whose objective is to identify and consolidate the main trends and challenges regarding CWBS sizing models. The method employed for the qualitative and quantitative survey of publications up to the year 2025 follows the guidelines of Parsifal, which is an online tool for data analysis and research. According to the study conducted, it was possible to obtain results that confirm the strong global research trend toward new sizing methods which, although mathematically more complex, were found to generate lower actual flow rates by 25% to 63% and, consequently, greater savings for the end customer.
Keywords: Cold Water; Design flow rate; Sizing models